Optimized β-Lactam Therapy Improves Survival in Carbapenem Non-Susceptible Gram-Negative Infections. (4th October 2017) - Flynt, Lauren K; Kenney, Rachel M; Veve, Michael; Pogue, Jason; Abreu-Lanfranco, Odaliz; Davis, Susan L
Abstract: Background: Infections due to carbapenem non-susceptible organisms are associated with significant mortality. The objective of this study was to identify modifiable predictors for survival in patients with these infections with a focus on antimicrobial therapies. Methods: This was a case–control study at a four-hospital health-system. Patients were evaluated for inclusion if they were ≥18 years with an infection due to a carbapenem non-susceptible organism from November 2013 to October 2016. Exclusion criteria were infections localized to the urinary tract or hospice designation. The primary objective was to identify independent predictors of all cause 30-day mortality. Pharmacodynamic (PD) optimized BL therapy was the exposure of interest, defined as doses administered to patients expected to obtain an estimated target attainment of ≥ ~90% of fT > MIC targets associated with a 1 log kill for the isolated pathogens MIC, based on published PK/PD literature and the renal function of the patient. Results: A total of 203 patients were included. Median age was 61 (49–70) and charlson comorbidity index was 2 (1–4). Forty-one (20%) had septic shock and 30-day mortality was observed in 63 (31%). P . A eruginosa was the causative pathogen in 149 (73%) of patients with Enterobacteriaceae representing the other 54 (27%). Lower respiratory tract infection were the most common ( n  = 128; 63%). Fifty-five patients received combination therapy (27%) with the most common combination consisting of BL and aminoglycoside (38%). Mortality was observed in 22% of patients receiving combination therapy compared with 35% monotherapy ( P  = 0.07). Forty-five percent of patients received a PD optimized BL, 25% received a BL not PD optimized, and 30% without a BL. Receipt of PD optimized BL and combination therapy were independent predictors of survival (table). Conclusion: PD optimized BL and combination therapy were associated with improved 30-day survival. Disclosures: S. L. Davis, Allergan: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant.